Timing and magnitude of regional right ventricular function and their relationship with early hospital mortality in patients with acute pulmonary embolism - (:unkn) unknown (TURKISH SOC CARDIOLOGY, 2019)
Objective: Right ventricular (RV) dysfunction in acute pulmonary embolism (APE) has been associated with increased mortality and morbidity. The aim of the present study was to assess the timing and magnitude of regional RV functions using speckle-tracking echocardiography (STE) and their relationship to early hospital mortality in patients with APE. Methods: One hundred forty-two patients were prospectively studied at the onset of an acute episode and after a median follow-up period of 30 days. Their clinical and laboratory characteristics were recorded. For all patients, conventional two-dimensional echocardiography and STE were performed within 24 h after the diagnosis of APE. Results: Twenty-eight (19.7%) patients died during the hospitalization follow-up. Patients who died during hospitalization were older and had higher high sensitivity cardiac troponin T levels, and a higher percentage of patients had simplified Pulmonary Embolism Severity Indexes. In STE analyses, they had lower RV free wall peak longitudinal systolic strain (PLSS) and higher RV peak systolic strain dispersion indexes. The time to PLSS difference between RV free wall and LV lateral was longer in patients who died during hospitalization than in those who survived, and this was an independent predictor of early hospital mortality with 85.7% sensitivity and 75.0% specificity in patients with APE. Conclusion: APE was associated with RV electromechanical delay and dispersion. Electromechanical delay index might be useful to predict early hospital mortality in patients with APE.
Keywords: pulmonary embolism; right ventricle; speckle-tracking echocardiography; SPECKLE-TRACKING ECHOCARDIOGRAPHY; RIGHT ATRIAL; DYSSYNCHRONY; STRAIN; VALIDATION; SOCIETY; MODEL